Caracterização geomorfológica e paleogeográfica da plataforma continental adjacente a foz do Rio Apodi-Mossoró, RN/Brasil - Lima, Samia Freire (2006)
The brazilian marginal basins have a huge potential to generate and accumulate petroleum. Incised valleys which are eroded in response to a fall of relative sea level are related to potential reservoir as well, modern drowned-valley estuaries serve as harbors to petroleum and salt industries, fisheries, waste-disposal sites and recreational areas for a significant fraction of the world s population. The combined influence of these factors has produced a dramatic increase in research on modern and ancient incised-valley systems. This research is one expression of this interest. The integrated use of satellites images and high resolution seismic (bathymetry, sides scan sonar) was used on the Apodi River mouth-RN to characterizes the continental shelf This area is located at the Potiguar Basin in the NE Brazilian Equatorial Atlantic margin. Through bathymetric and side scan sonar data processing, a digital Terrain Model was developed, and a detailed geomorphologic analysis was performed. In this way was possible to recognize the geomorphologic framework and differents sismofacies, which may influence this area. A channel extending from the ApodiMossoró river mouth to the shelf edge dominates the investigated area. This structure can be correlated with the former river valley developed during the late Pleistocene sea level fall. This channel has two main directions (NW-SE and NE-SW) probably controlled by the Potiguar Basin structures. The western margin of the channel is relatively steep and pronounced whereas the eastern margin consists only of a gentle slope. Longitudinal bedforms and massive ridges also occur. The first are formed doe to the shelf sediment rework and the reef-like structures probably are relics of submerged beachrock-lines indicating past shoreline positions during the deglacial sea-level rise. The sub-bottom seismic data allow the identification of different sismic patterns and a marcant discontinuity, interpreted as the Upper